VD_FINDINFO HC / 2012 / 699 vom 26. Oktober 2012 - VD Tribunal cantonal (2012)
AVOCAT D'OFFICE, INDEMNITÉEN GÉNÉRAL, FRAIS DE VOYAGE, DÉPLACEMENTSENS GÉNÉRAL, ASSISTANCE JUDICIAIRE | 122 al. 1 let. a CPC (CH), 2 al. 1 RAJ